The regulatory role of eosinophils in adipose tissue depends on autophagy - Aref Hosseini; Nina Germic; Nikita Markov; Darko Stojkov; Kevin Oberson; Shida Yousefi; Hans-Uwe Simon; Hans-Uwe Simon (Frontiers in Immunology, 2024)
IntroductionObesity is a metabolic condition that elevates the risk of all-cause mortality. Brown and beige adipose tissues, known for their thermogenic properties, offer potential therapeutic targets for combating obesity. Recent reports highlight the role of immune cells, including eosinophils, in adipose tissue homeostasis, while the underlying mechanisms are poorly understood.MethodsTo study the role of autophagy in eosinophils in this process, we used a genetic mouse model lacking autophagy-associated protein 5 (Atg5), specifically within the eosinophil lineage (Atg5eoΔ).ResultsThe absence of Atg5 in eosinophils led to increased body weight, impaired glucose metabolism, and alterations in the cellular architecture of adipose tissue. Our findings indicate that Atg5 modulates the functional activity of eosinophils within adipose tissue rather than their abundance. Moreover, RNA-seq analysis revealed upregulation of arginase 2 (Arg2) in Atg5-knockout eosinophils. Increased Arg2 activity was shown to suppress adipocyte beiging. Furthermore, we observed enrichment of the purine pathway in the absence of Atg5 in eosinophils, leading to a pro-inflammatory shift in macrophages and a further reduction in beiging.DiscussionThe data shed light on the importance of autophagy in eosinophils and its impact on adipose tissue homeostasis by suppressing Arg2 expression and limiting inflammation in adipose tissue.